NC Machining Simulation and Virtual Measurement of Spiral Bevel Gear based on the VERICUT - Zeng Hong; Yang Lin; Chen Yanyan; Wang Yanzhong (Jixie chuandong)
The NC machining simulation and virtual measurement of spiral bevel gear is carried out based on the VERICUT.Firstly,the coordinate transformation principle of traditional machine and NC machining principle are introduced.Then the tooth cutting simulations of the large gear of spiral bevel gear are carried out by using VERICUT.Secondly,the three-dimensional model is reversely built by means of UG software and the generated coordinates of tooth surface points.Finally,the simulation tooth cutting model is measured and contrasted with UG design model to verify the feasibility of NC processing method.Meanwhile,it also offers shortcuts to the actual NC machining of the gear,and greatly shortens the cycle from design to production,thus improving the production efficiency of spiral bevel gear.